Accounting for the neglected: Invertebrate species and the 2019–2020 Australian megafires. Issue 10 (31st May 2022) - Marsh, Jessica R.; Bal, Payal; Fraser, Hannah; Umbers, Kate; Latty, Tanya; Greenville, Aaron; Rumpff, Libby; Woinarski, John C. Z.
Abstract: Aim: Invertebrates make up the vast majority of fauna species but are often overlooked in impact assessment and conservation response. The extent to which the 2019–2020 Australian megafires overlapped with the range of vertebrate species has been well documented; consequently, substantial resourcing has been directed towards their recovery. Here, we attempt to document the extent of overlap of these megafires with invertebrate species. In doing so, we seek to demonstrate that it is possible and worthwhile to assess the effect of a catastrophic event on a large number of poorly known species. Location: Temperate and subtropical Australia. Time period: 2019–2020. Major taxa: Australian invertebrates. Methods: We adapted a published analytical pathway for the assessment of distributional fire overlap on vertebrate species. Overlaps with fire for 32, 163 invertebrate taxa were determined using point records and polygons. Results: We found that 13, 581 invertebrate taxa had part of their range burnt in the 2019–2020 Australian megafires. Of these, 382 taxa had the whole of their known range burnt, and a further 405 taxa had 50–99.9% of their range burnt. Five examples are described. Main conclusions: Poorly known groups of biodiversity can be impacted significantly by major disturbance events, but such impact is often overlooked. This oversight has the consequences of under‐estimating the magnitude of impacts and the potential failure to direct conservation responses to those species most in need of them. Our analysis demonstrates that the 2019–2020 megafires burnt ≥50% of the known range of nearly 800 Australian invertebrate taxa, a tally far higher than for vertebrates (19 taxa). Assessment of the real impact (i.e., beyond simply overlap with fire) requires more consideration of susceptibility and/or post‐fire survey and monitoring. The magnitude of overlap of the 2019–2020 megafires on invertebrate species justifies a conservation response that is less biased towards iconic vertebrate species.